TRIM44 links the UPS to SQSTM1/p62-dependent aggrephagy and removing misfolded proteins. Issue 4 (3rd April 2022) - Lyu, Lin; Chen, Zheng; McCarty, Nami
ABSTRACT: Until recently, the ubiquitin-proteasome system (UPS) and macroautophagy/autophagy were considered to be two independent systems that target proteins for degradation by proteasomes or via lysosomes, respectively. Here, we report that TRIM44 (tripartite motif containing 44) is a novel link that connects the UPS system with the autophagy degradation pathway. Suppressing the UPS degradation pathway leads to TRIM44 upregulation, which further promotes aggregated protein clearance through the binding of K48 ubiquitin chains on proteins. TRIM44 expression activates autophagy via promoting SQSTM1/p62 oligomerization, which rapidly increases the rate of aggregate protein removal. Overall, our data reveal that TRIM44 is a newly identified link between the UPS system and the autophagy pathway. Delineating the cross-talk between these two degradation pathways may reveal new mechanisms of targeting aggregate-prone diseases, such as cancer and neurodegenerative disease. Abbreviations : 3-MA: 3-methyladenine; ACTB: actin beta; ATG5: autophagy related 5; BB: B-box domain; BECN1: beclin1; BM: bone marrow; CC: coiled-coil domain; CFTR: cystic fibrosis transmembrane conductance regulator; CON: control; CQ: chloroquine; DOX: doxycycline; DSP: dithiobis(succinimidly propionate); ER: endoplasmic reticulum; FI: fluorescence intensity; FL: full length; HIF1A/HIF-1#x3B1;: hypoxia inducible factor 1 subunit alpha; HSC: hematopoietic stem cells; HTT: huntingtin; KD: knockdown; KD-CON: knockdown construct control; MM: multiple myeloma; MTOR: mechanistic target of rapamycin kinase; NP-40: nonidet P-40; NFE2L2/NRF2: nuclear factor, erythroid 2 like 2; OE: overexpression; OE-CON: overexpression construct control; PARP: poly (ADP-ribose) polymerase; SDS: sodium dodecyl sulfate; SQSTM1/p62: sequestosome 1; Tet-on: tetracycline; TRIM44: tripartite motif containing 44; UPS: ubiquitin-proteasome system; ZF: zinc-finger